Population Data Collection System in the Digital Era by Utilizing the Advantages of the Web to Improve Data Quality - Nabila Zahrani; Siti Amelia (International Journal of Smart Systems, 2023)
In the digital era, population data collection plays a vital role in effectively managing and utilizing demographic information. This paper presents a system for population data collection that leverages the advantages of web technology to enhance data quality. The system utilizes web-based platforms, specifically harnessing the power of the web and its associated technologies, such as PHP and MySQL. The system allows for real-time data collection, ensuring that demographic information is up-to-date and accurate. The advantages of web-based data collection methods include increased accessibility, enhanced efficiency, and the potential for real-time data updates. By leveraging the web, population data can be collected through online surveys, registration systems, and interactive data portals. These platforms allow for convenient data collection, ensuring broader participation and reducing geographical barriers. Through user-friendly web interfaces, individuals can easily input their personal data, eliminating the need for manual paper-based processes. This not only improves data accuracy but also improves efficiency in data collection. Furthermore, the system incorporates data validation mechanisms to ensure the integrity of the collected information. It employs automated validation processes to minimize errors and inconsistencies in the data. Additionally, the system includes security measures to protect the privacy of individuals' data, safeguarding against unauthorized access or data breaches. The use of web technology, particularly PHP and MySQL, in the population data collection system offers several benefits. These include improved data accuracy, real-time data updates, efficient data analysis, and enhanced accessibility for both data input and retrieval. Moreover, the system facilitates seamless integration with other data management systems, enabling better collaboration and information sharing. Overall, the implementation of a web-based population data collection system demonstrates the potential to leverage the advantages of web technology in enhancing data quality. By embracing digital solutions, organizations and institutions can streamline their data collection processes, ensuring more accurate and reliable demographic information for effective decision-making and policy formulation.